A Technique For Visualisation Of Latent Fingerprint Using Spirulina Powder On Electronic Surfaces - Sasipriya. G, Dr. Abirami Arthanari, Dr. S Rajeshkumar (Drugs and Cell Therapies in Hematology, 2021)
Aim: The study aims to visualize the latent fingerprint using spirulina powder on electronic surfaces. Introduction: A fingerprint is an impression left by the friction ridges of a human finger. The recovery of partial fingerprints from a crime scene is an important method of forensic science. Moisture and grease on a finger result in fingerprints on surfaces such as glass or metal. Latent prints can be found on a variety of surfaces; however, they are not readily visible and detection often requires the use of fingerprint powders, chemical reagents, or alternate light sources. Materials and methods: To develop latent fingerprints with the help of spirulina powder, few grams of pure commercially available spirulina powder was taken in the present study and then further ground in a blender to get a very fine powder to the level of talcum powder but no particle size was measured. Results: The development of latent fingerprints present on electronic surfaces like iPad, mobile, mobile charger, water purification machine, and electronic switch box-surface could be successfully done and gives clear ridges as is evident from the figures. Prints present on the skin could not be developed clearly in comparison to others may be due to lack of contrast. Conclusion: It is concluded that spirulina powder which is easily available, non-toxic and simple can be used successfully on electronic surfaces to develop prints in crime investigations.